Teachers' Readiness for English Language Teaching in the Post-Print Culture - Fathia, Rahma; Suparman, Asep; Hamzah, Amir (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
The rapid shift in English Language Teaching (ELT) from traditional print-based materials to digital and AI-based environments requires a comprehensive evaluation of teacher readiness. This study investigates ELT teachers' readiness for post-print pedagogy in four constructs: knowledge and skills, affective/beliefs, context, and behavior, and explores the influence of demographic variables. Using a quantitative, descriptive, and comparative design, 228 active English teachers in Indonesia participated via an online questionnaire. The findings reveal a "Digital Paradox" in which teachers have high cognitive and affective readiness, but show a much lower level of behavioral implementation (mean = 51.3), thus being categorized as "Low-Moderate Readiness" in actual practice. Demographic analysis using One-way ANOVA showed no significant differences in readiness by age, location, or school level (p > 0.05), indicating that challenges in the post-print era are experienced universally across teaching contexts. However, the Kruskal-Wallis test identified significant differences in teaching experience (p < 0.05), with mid-level teachers (8–15 years of experience) showing the highest readiness compared to novice and senior teachers. These results suggest that high theoretical knowledge does not automatically translate into classroom practice due to uneven institutional support and heavy curriculum demands. Therefore, policy interventions must move beyond merely theoretical digital literacy training to provide equitable technological infrastructure and ongoing pedagogical support to bridge the gap between teachers' potential and classroom realities.